Keratinocyte-Immune Cell Crosstalk in a STAT1-Mediated Pathway: Novel Insights Into Rosacea Pathogenesis - Deng, Zhili; Liu, Fangfen; Chen, Mengting; Huang, Chuchu; Xiao, Wenqin; Gao, Sini; Jian, Dan; Ouyang, Yuyan; Xu, San; Li, Jinmao; Shi, Qian; Xie, Hongfu; et al. (Frontiers in Immunology, 2021)
Rosacea is a common chronic inflammatory condition that mainly affects the central face. However, the molecular background of the normal central face and the transcriptional profiling and immune cell composition of rosacea lesions remain largely unknown. Here, we performed whole-skin and epidermal RNA-seq of central facial skin from healthy individuals, lesions and matched normal skin from rosacea patients. From whole-skin RNA-seq, the site-specific gene signatures for central facial skin were mainly enriched in epithelial cell differentiation, with upregulation of the activator protein-1 (AP1) transcription factor (TF). We identified the common upregulated inflammatory signatures and diminished keratinization signature for rosacea lesions. Gene ontology, pathway, TF enrichment and immunohistochemistry results suggested that STAT1 was the potential core of the critical TF networks connecting the epithelial–immune crosstalk in rosacea lesions. Epidermal RNA-seq and immunohistochemistry analysis further validated the epithelial-derived STAT1 signature in rosacea lesions. The epidermal STAT1/IRF1 signature was observed across ETR, PPR, and PhR subtypes. Immune cell composition revealed that macrophages were common in all 3 subtypes. Finally, we described subtype-specific gene signatures and immune cell composition correlated with phenotypes. These findings reveal the specific epithelial differentiation in normal central facial skin, and epithelial–immune crosstalk in lesions providing insight into an initial keratinocyte pattern in the pathogenesis of rosacea.